High Temperature Strength and Elastic Properties of Doped Ceria under Various Oxygen Partial Pressures. (2nd June 2015) - Taguchi, Takahiro; Watanabe, Satoshi; Sato, Kazuhisa; Hashida, Toshiyuki
Abstract : Fracture strength and Young's modulus of cerias doped with 10 mol.% Gd and 10, 20 and 30 mol.% Y and yttria stabilized zirconia were investigated by means of small punch testing method under controlled the temperature (1073 K) and the oxygen partial pressure (log((p(O2 )/atm)= -1.1, 17.5, -21.4, -22.0). Under the reducing conditions, the color of fractured doped ceria specimen changed from pale yellow to gray, by contrast, no oxygen partial pressure dependence of changes in color were observed on yttria stabilized zirconia. It is therefore indicated that oxygen nonstoichiometry affects mechanical properties of the doped ceria. Compared with the high oxygen partial pressure (log(p(O2 )/atm)= -1.1), under the low oxygen partial pressure the Young's modulus of all the specimens decreased monotonically. The fracture strength, by contrast, increased at log(p(O2 )/atm) = -17.5, and under the lower oxygen partial pressure, different variation trends showed each yttria doped cerias with Y contents. From scanning electron microscopy (SEM) observation, an increasing transgranular fracture was observed in the specimen at the fracture strength increasing region. The oxygen partial pressure dependence of the fracture strength of doped ceria could be arranged as a function of the reduction expansion of the lattice constant a / a 0, it has a maximum value at around a / a 0 = 0.30 %. It is suggested that there is a trade-off between weakening electrostatic bonding force caused by chemical expansion of lattice constant and strengthening caused by inhomogeneous structural change resulting from partial reduction of Ce 4+ to Ce 3+ .